29 Comparison between pure tachycardiomyopathy and acute heart failure and structural heart disease. (8th December 2021) - Stronati, Giulia; Urbinati, Alessia; Ciliberti, Giuseppe; Barbarossa, Alessandro; Falanga, Umberto; Silenzi, Marco; Principi, Samuele; Manfredi, Roberto; Compagnucci, Paolo; Casella, Michela; Russo, Antonio Dello; Guerra, Federico
Abstract: Aims: Tachycardiomyopathy (TCM) is a reversible cause of left ventricular dysfunction, secondary to rapid and/or asynchronous, irregular myocardial contraction. The disease can be divided in two main subgroups: arrhythmia-induced TCM also known as pure TCM, where the arrhythmia is the sole reason for the dysfunction, and impure TCM also known as arrhythmia mediated TCM, where the arrhythmia can exacerbate or worsen heart failure (HF) or an underlying heart disease. Pure TCM has already been described as affecting almost 1 out of 10 patients admitted for de novo acute HF. The aim of our study was to compare pure TCM and de novo acute HF and structural heart disease patients in terms of mortality and cardiovascular (CV)-related hospitalizations. Methods and results: Prospective, observational study enrolling all consecutive patients with a confirmed diagnosis of TCM and all patients admitted for de novo acute HF. The TCM diagnosis was suspected in all patients admitted for HF-related symptoms, an ejection fraction <50% with concomitant persistent atrial or ventricular arrhythmia, and confirmed after clinical and echocardiographic recovery. Acute HF diagnosis was made in all patients with an ejection fraction <50%, new HF-like symptoms, diagnosis of structural heart disease and no evidence of clinical or echocardiographic recovery. For each patient, all-cause death and CV-related hospitalizations were recorded. One-hundred-and-ten patients with TCM (61.8% males, 68 ± 13 years old) were propensity matched with a control population of patients with HF and structural heart disease (76.6% males, 71 ± 15 years old, 75% ischaemic heart disease). After a median follow-up of 5.1 years (1st–3rd quartile 2.6–7.0 years) TCM patients showed an overall higher estimate of survival when compared to HF patients (78% vs. 58%; P = 0.031; Figure 1A) but a lower estimate of time free from CV-related hospitalization (31% vs. 57%, P = 0.014; Figure 1B). TCM patients got most often readmitted for AF-related elective procedures (60.8% of all hospitalizations) such ablation procedures or elective cardioversion, TCM recurrence (13.7%), and elective coronary angiography (5.9%). On the other hand, HF patients got readmitted for HF worsening (40.9%), cardiac or vascular surgery (22.7%), and elective coronary angiography (9.1%). Propensity-score matched analysis confirmed the results for all-cause death (81% vs. 49%; P = 0.006) and CV-related hospitalizations (29% vs. 54%; P = 0.007). Conclusions: TCM is associated with higher rate of survival when compared to de novo acute HF, even after propensity score adjustment. On the other hand, patients with TCM got readmitted more frequently, requiring more often elective procedures in order to control the triggering arrhythmia.